Studi Penelitian Pengaruh Penambahan Limbah Serbuk Kuningan Terhadap Kuat Tekan Beton - Tenardhy Aryarama Wijaya (Fakultas Teknik dan Rekayasa, 2023)
Concrete is a structural element consisting of aggregate particles attached by a paste made from Portland cement and water. Brass powder waste is of particular concern, if left unchecked over time it will increase and accumulate, thus polluting the environment. One of its utilization is by making the waste as a concrete mixture material. This study aims to determine the compressive strength of normal concrete and concrete after adding brass powder at a percentage dose of 10% and 25% of the weight of fine aggregate. The method used in this study was an experimental method with a design concrete quality of 22 MPa, with 15 specimens. From the test results, the average compressive strength of normal concrete is 22.330 MPa. The average compressive strength of concrete with the addition of 10% brass powder by weight of fine aggregate was 20.962 MPa, decreased the compressive strength of concrete by 0.938%. The average compressive strength in concrete with the addition of brass powder of 25% by weight of fine aggregate is 23.736 MPa, experiencing an increase in compressive strength in concrete of 1.062% of the compressive strength in normal concrete